The Main Reasons for the Revival of Islam in Independent Kazakhstan - Sarsembayev, Ruslan M.; Rysbekova, Shamshiya S.; Assanova, Saltanat S.; Yesbolova, Moldir; Manasova, Ayzada S. (International Journal of Criminology and Sociology, 2022)
In the modern world history, we notice such phenomena as; globalization, digitalization, value pluralism, mass migration, terrorism, post-secularity, etc., which characterize the current nature of human civilization. Recently, among these trends, the phenomenon of the “revival of Islam” has emerged. Therefore, the systematic discussion relating to the phenomenon of Islam in the socio-cultural processes of the society has prevalent in religious studies. This topic has gained considerable attention by Kazakh researchers have also paid attention to this topic. The society of Kazakhstan has closely related to Islam in aspects of culture, history, personality, and morality. Since the collapse of the United Socialist Soviet Republics (USSR), Kazakhstan has gradually been becoming one of the fastest growing countries in Central Asia, focusing on modernization processes. Even though it follows secular nature of constitution, it has not only allowed the reentrance of traditional religious presence, but scholars have also noticed features of religious revival. Purpose of the article analyze the main factors that activated the mass- revival of Islam within the Kazakh society after the country’s independence. Leading methods − conceptual analysis, structural analysis, and comparative analysis. Thanks to a systematic generalization of domestic and foreign researchers’ views, as well as sociological data, it became possible to form common knowledge about the causes of the revival of Islam in Kazakhstan.